P Pengobatan Terkini Alergi, Reaksi Toksik, Dan Penyakit Akibat Artropoda - Reqgi First Trasia (LPPM Universitas Sari Mulia, 2021)
Abstract Background: The presence of erusism and lepidopterism cases in Indonesia is influenced by butterfly species, regional conditions and community habits as farmers or garden workers. In addition, the population of house dust mites depends on several factors that are still being studied. Parasitological reviews of current treatments for insect disease are still poorly understood. Purpose: This article aims to review current treatments for allergies, toxic reactions, and insect-borne diseases. Methods: Recent literature search, obtained 11 relevant articles for review. Results: Local treatment due to contact with insects can be given a solution of iodine, corticosteroids and antihistamines. In severe cases, the drug can be given orally or parenterally. Conclusion: Based on the results of the review, it can be concluded that to treat airway attacks due to mite allergy, bronchodilators and corticosteroids can be given.